(untitled) (Applied Biological Research, 2015)
The present study was aimed to assess the impact of foliar application of various micronutrients viz., Fe, Zn, Mn, B and Mo, sprayed individually and in combination, on the qualitative characteristics of mulberry leaves. The experiment was conducted in 2011-2012 and quality parameters assessed 45 days after pruning. The results revealed that all the individual applications of above micronutrients significantly improved moisture, moisture retention capacity, chlorophyll ‘a’ and ‘b’ and total chlorophyll, carotenoids, nitrogen, phosphorus, potassium, zinc, iron, boron, manganese, crop growth rate and net assimilation rate over control. The combined foliar application of 0.5% ZnSO4 + (1.0% FeSO4 + 0.1% citric acid) + 0.2% boric acid+ 0.5% MnSO4 + 0.01% Na2MoO4 was most effective in improving mulberry leaf quality.